UNDERSTANDING NANO-BIO-INTERACTIONS WITH CORRESPONDING BIOLOGICAL RESPONSES: INSIGHTS AND IMPACT ON NANO ASSEMBLY AND DISASSEMBLY - JOSHI, POONAM; SUYAL, JYOTSANA; PARASHAR, TARUN; RAWAT, SHIVANI (International Journal of Applied Pharmaceutics, 2025)
Using stimuli-responsive Bio Interactions with controlled nano-assembly is proving a potent method for generating theranostic nanosystems that satisfy the needs of modern medicine for example, targeted delivery which is very helpful for cancer treatment with minimum side effects. However, because of the limitations in our knowledge, this promising topic is still in the proof-of-concept stage. This study provides an overview of the most recent theoretical and experimental advancements in biological fate, functional activity of nano-assemblies, and nano-bio interactions with exogenous stimulus-triggered systems (Light-responsive systems, Ultrasound-responsive systems, Magnetic field-responsive systems, and Thermal-responsive systems)endogenous stimulus-triggered systems (Ph-Responsive Systems, Redox-responsive systems, Enzyme-responsive systems) and multi stimuli system. Related biological consequences reactions. Firstly, we intend to thoroughly explain these relationships in this review. The relationship between interaction studies and nano-based stimuli; the important physicochemical characteristics of in vivo stimuli, such as responsive assembly and disassembly; biological applications; and pharmacokinetic (pk) parameters based on nano-bio interaction.